Revisiting the role of hypoxia-inducible factors and nuclear factor erythroid 2-related factor 2 in regulating macrophage inflammation and metabolism - Ting, Kenneth K. Y. (Frontiers in Cellular and Infection Microbiology, 2024)
The recent birth of the immunometabolism field has comprehensively demonstrated how the rewiring of intracellular metabolism is critical for supporting the effector functions of many immune cell types, such as myeloid cells. Among all, the transcriptional regulation mediated by Hypoxia-Inducible Factors (HIFs) and Nuclear factor erythroid 2-related factor 2 (NRF2) have been consistently shown to play critical roles in regulating the glycolytic metabolism, redox homeostasis and inflammatory responses of macrophages (Mφs). Although both of these transcription factors were first discovered back in the 1990s, new advances in understanding their function and regulations have been continuously made in the context of immunometabolism. Therefore, this review attempts to summarize the traditionally and newly identified functions of these transcription factors, including their roles in orchestrating the key events that take place during glycolytic reprogramming in activated myeloid cells, as well as their roles in mediating Mφ inflammatory responses in various bacterial infection models.